2013
DOI: 10.7567/jjap.52.09kf02
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Composition Variation of Ferroelectric Phase Transition Temperature in (Ba,Ca)TiO3 by Synchrotron Radiation Powder Diffraction

Abstract: The ferroelectric cubic–tetragonal phase transition temperature T C in (Ba1-x Ca x )TiO3 (BCT) is almost unchanged and is maximum at x ∼0.06 in the T–x phase diagram, in contrast to many other lead-free BaTiO3-based solid solutions that show a decrease in T C by atomic substitution. To investigate the peculiar atomic substitution effect in BCT, the crystal structure parameters and electron density distributions of BCT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The cubic variant ( c ) 3 occurs e.g. in SrTiO 3 with space group Pm $\bar{3}$ m 14. The crystal structure features a three dimensional network of corner‐shared [TiO 6 ] octahedra, whereas the [SrO 12 ] cuboctahedra are octahedrally connected with each other by common square faces.…”
Section: Discussionmentioning
confidence: 99%
“…The cubic variant ( c ) 3 occurs e.g. in SrTiO 3 with space group Pm $\bar{3}$ m 14. The crystal structure features a three dimensional network of corner‐shared [TiO 6 ] octahedra, whereas the [SrO 12 ] cuboctahedra are octahedrally connected with each other by common square faces.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Substitution of Ca 2+ is accompanied by a linear decrease in the cubic a lattice parameter, 36 which would suggest a depression in the T c , such as is observed in the BaTiO 3 -SrTiO 3 solid solution. 37 This has been attributed globally to a size mismatch effect of the Ba 2+ and Ca…”
Section: 35mentioning
confidence: 99%
“…16) This result made a contrast with the fact that the small T C change 19) and no apparent change in Ti-O bonding nature were observed in the (Ba 1−x Ca x )TiO 3 system. 20) The careful crystal structure analysis of (Ba 1−x Gd x )(Ti 1−x=2 Mg x=2 )O 3 revealed that Gd ions occupied the six 〈100〉 off-centered positions in the cubic phase of (Ba 1−x Gd x )(Ti 1−x=2 Mg x=2 )O 3 (0 < x ≤ 0.3) and the single site shifted along the [001] direction in the tetragonal phase of (Ba 0.94 Gd 0.06 )(Ti 0.97 Mg 0.03 )O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…16) This result made a contrast with the fact that the small T C change 19) and no apparent change in Ti-O bonding nature were observed in the (Ba 1−x Ca x )TiO 3 system. 20) The careful crystal structure analysis of (Ba…”
Section: Introductionmentioning
confidence: 99%